THE PROCEDURE OF THE SLIP MODELS OF POLYCRYSTALLINE PLASTICITY IN THE GENERAL CASES - Dan, Bui Huu (Vietnam Journal of Mechanics, 1992)
The computation procedure of the slip model of polycrystalline plasticity was extended for the most general cases, when the stress and strain state are expressed in the five-dimension vector space this extent ion is based on the know ledges of Clifford algebra in the many-dimension (more than 3) vector space. The results would be reduced into the old results given in the more simple cases.